PERANCANGAN MODEL APLIKASI PENJUALAN MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT DAN SYSTEM DEVELOPMENT LIFE CYCLE : Studi Kasus Di Sentra Batik Tulis Giriloyo - Meita Sulistyani (2021)
Giriloyo batik village is a center for written batik in Giriloyo hamlet, Wukirsari village, Imogiri Bantul district, Yogyakarta. This Giriloyo batik village produces hand-drawn batik cloth with natural and synthetic coloring. Based on data from the financial department of the Giriloyo batik village, sales of batik products in Giriloyo have decreased by 67.78%. Based on these problems, the researcher proposes to design a sales application model as an alternative to selling batik products. This study aims to determine the features required by visitors of Giriloyo written batik for the sales application. The method used in this research is Quality Function Deployment to determine consumer needs and the Development Life Cycle system for designing application models. The results obtained from this study are a list of consumer needs for sales applications, namely "Shopping through the application", "Balance for transactions", "There is discount information", "There is reference information on the use of written batik models", "There is information on learning batik", " There is information on directions to the village of Giriloyo batik "," There is information about the profile of the Giriloyo batik village "," Application security "," Interesting appearance ". For application features, namely shop features, epay features, discount information, batik of the day, nyanting, locator features, my batik features, account features and attractive designs.